Kapasitas Reproduksi Mencit Betina (Mus musculus L.) Setelah Pemberian Infus Batang Tabat Barito (Ficus deltoidea Jack.) - Aditya K. Karim (Jurnal Biologi Papua, 2011)
Tabat barito (Ficus deltoidea Jack.) is vastly used to induce sexual aroused (aphrodisiacs) and effect on female reproductive organ. The aim of this research was performed to examine the effects of bark tabat barito infuse on reproductive capacities female mice. Fifteen of female mice were devided randomly into 5 groups, respectively. The treatment dosages were control, placebo, 50%, 75% and 100%. Infuse and aquades administrated orally 0.5 ml/hari for 5 estrouse cycles. Female mice were mated (1:3). At the eighteen days of gestation, female mice were sacrificed and observed, covered the weight of mice, uterus, liver; the total number of fetus, their weight and length body. The statistical analysis was performed using ANOVA and DMRT test. The result of this study indicated that infuse of bark tabat barito (Ficus deltoidea Jack) increasing the reproductive capacities but no significant. The weight of mice, uterus, liver between control and treatment no different (P> 0.05) but for total number of fetus in control 8.00 + 1.00, whereas dosages 50%, 75% and 100% were 8.67 + 0.58, 11.67 + 1.16 and 10.00 + 1.00, respectively. In total number of fetus different in 70% dosage to others, and total number of fetus in 100% dosage are significant different with control and 70% dosage.Key words: Tabat barito, aphrodisiacs, progesterone, reproductive capacities.